2023
DOI: 10.29026/oes.2023.230014
|View full text |Cite
|
Sign up to set email alerts
|

Vectorial spin-orbital Hall effect of light upon tight focusing and its experimental observation in azopolymer films

Alexey Porfirev,
Svetlana Khonina,
Andrey Ustinov
et al.

Abstract: Hall effect of light is a result of symmetry breaking in spin and/or orbital angular momentum (OAM) possessing optical system and is caused by e.g. refractive index gradient/interface between media or focusing of a spatially asymmetrical beam, similar to the electric field breaking the symmetry in spin Hall effect for electrons. The angular momentum (AM) conservation law in the ensuing asymmetric system dictates redistribution of spin and orbital angular momentum, and is manifested in spin-orbit, orbit-orbit, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In non-Majorana devices, it has been experimentally demonstrated that Cooper pairs can be split into spin-entangled electrons flowing in two spatially separated normal metals, resulting in a positive current-current correlation. [26][27][28][29][30][31] Although there are many theoretical studies devoted to investigate the property of noise CC induced by MBSs, [32][33][34][35][36][37][38][39] the Majoranamodulated nonlocal transport has not been reported up to date. One of the possible reasons is that the Majorana energy splitting, which is essential to induce the noise CC, is generally weak and approaches to zero in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…In non-Majorana devices, it has been experimentally demonstrated that Cooper pairs can be split into spin-entangled electrons flowing in two spatially separated normal metals, resulting in a positive current-current correlation. [26][27][28][29][30][31] Although there are many theoretical studies devoted to investigate the property of noise CC induced by MBSs, [32][33][34][35][36][37][38][39] the Majoranamodulated nonlocal transport has not been reported up to date. One of the possible reasons is that the Majorana energy splitting, which is essential to induce the noise CC, is generally weak and approaches to zero in some cases.…”
Section: Introductionmentioning
confidence: 99%